Analysis of the Composite Transmission of Magnetorheological Fluids and Shape Memory Alloy - Chen Song; Jian Kailin; Huang Jin; Huang Xia (Jixie chuandong)
The magnetorheological effect of magnetorheological fluid reduce under a high temperature condition,which causes so many problems like the uncontrollability of the variation of shearing stress,and even failure of the transmission device.Based on the rheological property of magnetorheological fluid and the temperature characteristics of shape memory alloy,a composite transmission device of magnetorheological fluid and shape memory alloy is designed,which rely on magnetorheological fluid to transfer torque under a lower temperatures condition,shape memory alloy spring assisted power transmission when the magnetorheological performance reduce under a high temperature condition.The performance of drive force transmission device is analyzed,and the formula of power transmission of transmission device is derived.The study results show that the composite transmission device can work at the external magnetic field and the temperature control,the torque can maintain continuous,controllable under a high temperature condition,the stability and efficiency of transmission device are improved.